Unraveling the role of ataxin-2 in metabolism - Carmo-Silva, Sara (2019)
Ataxin-2 is a polyglutamine protein implicated in several biological processes such as RNA metabolism and cytoskeleton reorganization. Ataxin-2 is highly expressed in various tissues including the hypothalamus, a brain region that controls food intake and energy balance. Ataxin-2 expression is influenced by nutritional status. Emerging studies discussed here now show that ataxin-2 deficiency correlates with insulin resistance and dyslipidemia, an action mediated via the mTOR pathway, suggesting that ataxin-2 might play key roles in metabolic homeostasis including body weight regulation, insulin sensitivity, and cellular stress responses. In this review we also discuss the relevance of ataxin-2 in the hypothalamic regulation of energy balance, and its potential as a therapeutic target in metabolic disorders such as obesity.